PENGARUH PEMBERIAN EKSTRAK TAUGE DITAMBAH MADU TERHADAP KUALITAS SPERMATOZOA MENCIT JANTAN (Mus musculus L.) - Wena Diartha, I Wayan; Sudatri, Ni Wayan; Setyawati, Iriani (SIMBIOSIS, 2016)
Bean sprouts, vegetables that are often consumed, contain vitamin E, C, riboflavin, niacin, folate, and some minerals such as selenium, manganese, zinc and iron. Honey contains monosaccharide i.e. fructose, sucrose, glucose, and maltose. This study aimed to investigate the effect of bean sprout extract added with honey to the spermatozoa quality of male mice and the most concentration that affected. This research used a completely randomized design (CRD). Twenty male mice divided into four groups: control (aquadest), P1 (25 mg/g BW bean sprout extract + 0.07 ml honey), P2 (50 mg/g BW bean sprout extract + 0.07 ml honey) and P3 (75 mg/g BW bean sprout extract + 0.07 ml honey). The extracts were given 0.3 ml/mice/day for 30 days. The variables that are observed were spermatozoa motility, morphology, viability and also amount of spermatozoa. Data were analyzed with one way ANOVA and followed by Duncan Multiple Range Test (DMRT). The results showed that bean sprout extracts added with honey gave positive effects by increasing type A motility of spermatozoa but decreased type D motility. The treatments also increased the amount of spermatozoa significantly. However, 75 mg/g BW bean sprout extract + 0.07 ml honey did not affect spermatozoa morphology and viability of male mice (Mus musculus L.). The optimal dose that affected sperm quality in this research was 50 mg/g BW bean sprout extract + 0.07 ml honey. Keywords : honey, Mus musculus L, bean sprout extracts, the quality of spermatozoa
Keywords: honey, Mus musculus L, bean sprout extracts, the quality of spermatozoa